An Analysis of Figurative Meaning Translation in “Just Give Me a Reason” - Ririn Tasumbey; Indah Afrianti; Dewa Made Agustawan (Saniya Institute, 2025)
Figurative meaning often presents challenges in translation, especially in song lyrics where meaning, emotion, and artistic expression must be conveyed simultaneously. This study examines the translation methodology for the figurative meanings in the bilingual song lyrics “Just Give Me a Reason” by Pink featuring Nate Ruess and its Indonesian version, “Berilah Aku Satu Alasan.” The objective of this research is to identify the types of figurative expressions used in the original lyrics and to analyze the translation methods applied in rendering them into Indonesian. This study employs a qualitative descriptive method. The data consist of figurative expressions found in the English lyrics and their corresponding translations in Indonesian. The analysis focuses on how the figurative meanings are transferred and whether the original sense is maintained. The findings reveal that several translation methods are used, including literal translation, adaptation, and paraphrasing. While some figurative expressions are preserved, others are modified to achieve naturalness and clarity in the target language. In conclusion, the translator employs flexible methods to balance meaning accuracy and lyrical acceptability.